The Use of Digital Library for Tourism Promotion Through Tourism Object Transliteration into Katakana and Lontara Letter - Kasmawati; Burhan Kadir; Agussalim; Renold; Firmansyah; Muh. Bintang Rahmadhani Antasar (Politeknik Pariwisata Makassar, Indonesia, 2023)
This study intends to improve the comprehension and knowledge of local tourists and Japanese foreign tourists in order to promote South Sulawesi's tourism attractions by making the best use of digital dictionaries. this study tries to describe the design concept of an Android-based Katakana and Lontara tourist attraction digital dictionary application. This study employs a qualitative descriptive methodology to describe the style of katakana and lontara letter transliteration of tourism destination names. This study revealed that there are several steps taken in transliterating the names of tourist objects. This study suggested that this application can serve as a guide for foreign tourists not only online, but also offline in order to reduce quota/network usage.